Carbon-nanotube-deposited photonic crystal fiber for refractive index sensing - Tou, Z. Q. (2014)
We present a novel fiber optic sensor based on the assembly of a thin film of carbon nanotubes (CNTs) onto a short length of photonic crystal fiber (PCF) which is spliced between two single mode fibers (SMFs). The assembly of the thin film was achieved via a simple and effective deposition method. The deposition of CNTs modified the sensing ability of the sensor, allowing it to work in the intensity encoding scheme, thus opening the sensor to the possibility of dual parameter sensing. The sensor exhibited a sensitivity of 36.1 dB/ RIU and 96.6 dB/ RIU within the ranges of 1.33-1.38 and 1.38-1.42 respectively.